The reliability and validity of the bar-mounted PUSH BandTM 2.0 during bench press with moderate and heavy loads. Issue 23 (2nd December 2019) - Lake, Jason; Augustus, Simon; Austin, Kieran; Comfort, Paul; McMahon, John; Mundy, Peter; Haff, G. Gregory
ABSTRACT: The aim of this study was to assess the reliability and validity of the bar-mounted PUSH Band TM 2.0 to determine peak and mean velocity during the bench press exercise with a moderate (60% one repetition maximum [1RM]) and heavy (90% 1RM) load. We did this by simultaneously recording peak and mean velocity using the PUSH Band TM 2.0 and three-dimensional motion capture from participants bench pressing with 60% and 90% 1RM. We used ordinary least products regression to assess within-session reliability and whether the PUSH Band TM 2.0 could accurately predict motion capture velocity. Results showed that PUSH Band TM 2.0 and motion capture peak and mean velocity reliability was acceptable with both loads. While there was a tendency for the PUSH Band TM 2.0 to slightly overestimate peak and mean velocity, there was no fixed bias. However, mean velocity with 60 and 90% 1RM demonstrated proportional bias (differences between predicted and motion capture values increase with magnitude). Therefore, PUSH Band TM 2.0 peak velocity with 60 and 90% 1RM is valid, but mean velocity is not.